2021
DOI: 10.1007/s10924-021-02304-1
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization and Toughening of Biodegradable Polylactic Acid/Cellulose Acetate Films by Polyamide Amine Dendrimers

Abstract: Due to the poor compatibility caused by the large difference in hydrophilicity and interface between polylactic acid (PLA) and cellulose acetate (CA), the blending of the two materials is di cult and the application is limited. To solve this problem, a type of polyamide amine (PAMAM) dendrimer was introduced to modify PLA / CA blends in this work. The results showed that PAMAM could improve the compatibility of PLA / CA blends, promote the distribution of CA and crystallization of PLA. At the same time, adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…ES in drug delivery mainly includes sequential ES, 141 synchronized ES, 142 coaxial ES, 143 and side-by-side ES 144 ( Fig. 8 and Table 7 ).…”
Section: Functionality Of Electrostatically Spun Nanofiber Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…ES in drug delivery mainly includes sequential ES, 141 synchronized ES, 142 coaxial ES, 143 and side-by-side ES 144 ( Fig. 8 and Table 7 ).…”
Section: Functionality Of Electrostatically Spun Nanofiber Materialsmentioning
confidence: 99%
“…Yang et al 155 developed a detachable triaxial spinneret to direct three ES fluids for the preparation of a series of nucleosheath nanostructures. The three fluids used for ES consisted of a common solvent (outer fluid), an electrospinnable dilute cellulose acetate (CA) 143 solution (intermediate fluid), and an electrospinnable ibuprofen–methanolysin solution (inner fluid), which led to the formation of an ibuprofen/methanolysin amorphous solid dispersion coated with a thin layer of CA, and the thickness of the coating could be adjusted by precisely adjusting the CA concentration of the intermediate solution. Experimental results show that single ibuprofen/myristolol protein fibers produce an initial burst release, but this release is eliminated in systems with CA coatings, and this tunable way of precisely manipulating drug release provides a new approach for the development of advanced functional nanomaterials, which can be controlled by the process nanostructure in triaxial ES property relationship to control their performance.…”
Section: Functionality Of Electrostatically Spun Nanofiber Materialsmentioning
confidence: 99%
“…Huang and coworkers studied how in incorporation of polyamide amine (PAMAM) compatibilizer influences the performance of PLA/CA-based materials. 15 It was reported that a certain content of PAMAM could enhance the compatibility of these two polymers contributing to better mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from tensile test and microstructure analysis revealed the compatibilization effect of this grafted copolymer as tensile stress at break was improved and finer morphology with enhanced adhesion between two phases was observed. Huang and coworkers studied how in incorporation of polyamide amine (PAMAM) compatibilizer influences the performance of PLA/CA‐based materials 15 . It was reported that a certain content of PAMAM could enhance the compatibility of these two polymers contributing to better mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…35 In our previous studies, the PLA/CA blends were modified with polyamide amine (PAMAM) dendrimers to obtain good compatibilization and toughening effects. 36 However, the compatibilization effect of hyperbranched polymers on blends depends on intermolecular hydrogen bonds and polar groups. If the polarity is relatively weak, the interfacial stability and compatibilization may be poor because the formed hydrogen bonds may not be sufficient for the formation of the cross-linked entanglement network.…”
Section: Introductionmentioning
confidence: 99%